1437. Biochemical characterization of L1 and L2 β-lactamases from clinical isolates of Stenotrophomonas maltophilia. (31st December 2020) - Mojica, Maria F; Rutter, Joseph; Taracila, Magdalena A; Papp-Wallce, Krisztina M; Spencer, James; Vila, Alejandro J; Bonomo, Robert A
Abstract: Background: Stenotrophomonas maltophilia is a Gram-negative, non-fermenting opportunistic pathogen. Two β-lactamases provide intrinsic resistance to β-lactams: a class B Metallo- β-lactamase L1, and a class A serine β-lactamase (SβL) L2. Recently, we described novel variants of the L1 and L2 in a collection of clinical S. maltophilia isolates collected in the US, and showed through analyses of the amino acid sequences that L1 and L2 grouped into 4 (A-D, B, C, and E) and 2 (A and D) clades, respectively. We aimed to characterize the new L1 and L2 clinical variants biochemically. Methods: Representative bla L1 and bla L2 genes from each of the identified clades were cloned into pBC-SK and pET24 vectors and transformed into E. coli DH10B and BL21 (DE3) cells, respectively. Minimal inhibitory concentrations (MICs) were determined using CLSI approved methods. Cell-based assays and biochemical characterization performed on purified enzymes, including circular dichroism (CD), thermal stability, and steady-state kinetics assays, were performed. Results: Susceptibility testing results using DH10-B E. coli strains expressing the L1 and L2 variants are shown in Table 1. Remarkably, while all L1 variants confer the same level of resistance to carbapenems, L2B conferred higher MICs to 3rd gen cephalosporins and aztreonam than L2D. Kinetics assays confirmed differences in the k cat of both enzymes to ceftazidime (32s-1 for L2B vs. 7s-1 for L2D) and avibactam inhibition constant K i (1.7 μM for L2B vs. 4.5 μM for L2D). Structurally, L2B and L2D present distinctive CD spectra and thermal stabilities ( Δ Tm 5°C). Table 1 Conclusion: As opposed to the L2 variants, our results suggest that the L1 variants may not be functionally nor structurally different. Differences between L2B and L2D might have arisen due to the use of cephalosporins and SβL inhibitors. Further experiments are on the way to determine the structural basis of these observations and the implication of these for the design of novel β-lactamase inhibitors. Disclosures: Krisztina M. Papp-Wallce, PhD, Entasis (Grant/Research Support)Merck (Grant/Research Support)Venatorx (Grant/Research Support) Robert A. Bonomo, MD, Entasis, Merck, Venatorx (Research Grant or Support)